Music Composition Makules | Komposisi Musik Makules - Kadek Agus Pusaka Adiputra; Tri Haryanto (GHURNITA: Jurnal Seni Karawitan, 2022)
Makules' musical works are based on a phenomenon where composers in Bali, especially those in the setting environment, in the Tabanan area, in creating new musical compositions are more dominant in processing musical elements such as rhythm, melody, dynamics, and harmony. Few composers work on timbre or timbre. From this phenomenon, the stylist gets inspiration to do something different. Obsession leads to abstraction of thought with an interest in processing sound color, creating a new impression by modifying timbre or sound color as the direction of creation. Therefore, a musical work in the form of experimental music was made with the title Makules. The meaning of the title Makules is seen from the word Makules which means changing skin, where the stylist uses the title according to its meaning which means changing skin.